Effects of transportation on gastric pH and gastric ulceration in mares - Barbara Padalino; Georgina L. Davis; Sharanne L. Raidal (Journal of Veterinary Internal Medicine, 2020)
Abstract Background Transportation has been suggested as a risk factor for gastric ulceration in horses, but limited evidence supports this assumption. Animals Twenty‐six Standardbred, Thoroughbred, and Warmblood mares from a university teaching herd. Methods Twelve mares were confined for 12 hours, overnight, in reproductive stocks with indwelling nasogastric tubes (NGTs) to assess pH of gastric fluid (GF). Gastric ulceration was assessed endoscopically before and after confinement. Subsequently, 26 horses were transported for 12 hours, overnight, in 2 consignments. During transportation, GF was aspirated from indwelling NGT placed in the same 12 mares used in the confinement study, and gastric ulceration was assessed endoscopically before and after transportation in all horses. Results The median pH of GF in confined horses was 1.70‐2.49 at each sampling point, and there was no apparent effect on gastric squamous ulcer scores. The median pH of GF from the same 12 horses at corresponding sampling times during transportation was 6.82‐7.22. Transportation was associated with increased gastric squamous ulcer scores, particularly in horses fasted for gastroscopy and NGT placement immediately before departure. Gastric emptying appeared delayed after transportation in horses fed before departure. Conclusions and Clinical Importance Transportation is associated with increased gastric squamous ulceration and with increased pH of GF. These findings may be a consequence of impaired gastric emptying and reflux of alkaline small intestinal content, with factors such as duodenal bile salts and short‐chain fatty acids mediating mucosal injury.